2012
DOI: 10.5505/tjtes.2012.49225
|View full text |Cite
|
Sign up to set email alerts
|

A patient who was burned in the operative field: a case report

Abstract: Ameliyat alanı yangınları oldukça nadirdir. Yine de, bir felaket, hemen hemen her türlü cerrahiyi güçleştirebilir. Ameliyat alanı yangınlarının çoğunluğu, oksijenden zengin bir ortamda alkol bazlı cerrahiye hazırlama solüsyonları-nın, elektrikli cerrahi ekipmanın veya kolay tutuşan kumaş-ların kullanılmasından kaynaklanmaktadır. Biz, over kisti ve uterin miyomları nedeniyle jinekolojik cerrahi geçirir-ken alev yanığına maruz kalan hastayı sunuyoruz.Anahtar Sözcükler: Alev; alev yanığı; ameliyathane; alkol bazl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…14 Clinically, several case reports and two case series of surgical fires because of alcohol-based skin preparation have been recorded in various surgical fields. [15][16][17][18][19][20] One case series 19 from the United Kingdom between 2004 through 2011 found that 11/13 surgical fires were attributed to alcohol-based skin preparations. The authors concluded that surgical fires continue to occur despite precautions written in the warning labels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Clinically, several case reports and two case series of surgical fires because of alcohol-based skin preparation have been recorded in various surgical fields. [15][16][17][18][19][20] One case series 19 from the United Kingdom between 2004 through 2011 found that 11/13 surgical fires were attributed to alcohol-based skin preparations. The authors concluded that surgical fires continue to occur despite precautions written in the warning labels.…”
Section: Discussionmentioning
confidence: 99%
“…In labs, surgical fires with porcine skin have been noted when using alcohol‐based skin preparation when allowing for 3 min of drying (the standard waiting period) in 10% of cases without pooling and in 25% of cases with pooling 14 . Clinically, several case reports and two case series of surgical fires because of alcohol‐based skin preparation have been recorded in various surgical fields 15–20 . One case series 19 from the United Kingdom between 2004 through 2011 found that 11/13 surgical fires were attributed to alcohol‐based skin preparations.…”
Section: Discussionmentioning
confidence: 99%